Raina's story - McDaniel, Lurlene (New York : Delacorte Press, 2005)
After sixteen-year-old Raina learns that she is a perfect match for donating bone marrow to a leukemia patient in Virginia, she discovers that the young woman is the sister she never knew she had.
Accelerated Reader AR
Keywords: Interpersonal relations -- Fiction; Mothers and daughters -- Fiction; Sisters -- Fiction; Leukemia -- Fiction; Friendship -- Fiction; Christian life -- Fiction; Florida -- Fiction; Virginia -- Fiction